Study of the double rebuilding effect of the nonstationary longitudinal wave in rod with rectangular cross section - Егармина, Лариса Николаевна (Technology audit and production reserves, 2015)
The article investigates obtained by the author new effect of a dual modification of non-stationary wave in a rod with rectangular cross section. The dynamics of rod is described by derived earlier improved one-dimensional dynamic equations of the longitudinal deformation. This equations were got basis on strict mathematical algorithm (so-called non-minimal simplification of the three-dimensional dynamic equations of the theory of elasticity) – “asymptotic-group” analysi. On the solutions of mentioned equations were built graphs of the longitudinal wave distribution in the rod. Analysis of them allowed to describe tridimentionality of the process. At the same time the transfer of three-dimensional state of strain to one-dimensional classic case followed by arising of the appropriate quasifronts is studied. Also must pay attention to the fact that all wave fronts velocities are the same as in the problems of theory of elasticity.